P-118 Investigating anaemia and targeting treatment in a hospice population: a quality improvement project. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Steele, Tom; Bonwick, Helen; Chapman, Laura
Abstract : Background: Anaemia is common in palliative care. Results of the national audit of blood transfusion practice in hospices, published (online first) last year, recommended more rigorous investigation of anaemia and increased use of alternative therapies (Neoh, Gray, Grant-Casey, Estcourt et al ., 2019). This project aimed to improve the proportion of patients with anaemia at Marie Curie Hospice Liverpool having haematinic investigations and receiving appropriate, targeted therapies. Methods: Several changes have been implemented through this project. To raise awareness, education sessions were delivered and practical written guidance on performing and interpreting haematinic investigations disseminated. A protocol was implemented to ensure outpatients attending for blood transfusions had investigations completed. Finally, an electronic template was developed to prompt investigating and recording results. Between August 2018 and February 2019 continual retrospective analysis was performed using laboratory and patient records. All patients who had haemoglobin checked at the hospice had clinical details, haematinic tests (ferritin, iron studies, B12 and folate; if performed within 6 weeks before or 2 weeks after) and resulting treatments recorded. Results: 125 patients with anaemia were assessed over the project (excluding repeat sampling). Amongst those having blood transfusion, assessment of both iron status and B12/folate improved from 2/12 (17%) in the first two months to 7/7 (100%) in the last two months of the project. Including all patients with Hb <100 g/dL, iron status assessment improved from 7/22 (32%) to 12/18 (67%) and B12/folate from 5/22 (23%) to 9/18 (50%). Results led to alternative therapies in 13 cases: oral iron (n=5), intravenous iron (n=6) and folic acid (n=2). Conclusions: This quality improvement project has led to more patients being investigated for underlying causes of anaemia and increased usage of targeted therapies. Research is required to establish if this approach impacts symptoms or transfusion utilisation and the role of specific treatments, particularly intravenous iron therapy, in this population.